COVID-19 era: time for temporary mechanical circulatory support?. (26th April 2021) - Alonso Fernandez De Gatta, M; Diego Nieto, A; Merchan Gomez, S; Gonzalez Cebrian, M; Toranzo Nieto, I; Martin Herrero, F; Barrio, A; Rodriguez Estevez, L; Sanchez, PL
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): Instituto de Salud Carlos III in Spain (Co-funded by European Social Fund "Investing in your future"). INTRODUCTION The Coronavirus disease 19 (COVID-19) pandemic has impacted clinical practice with important changes in the most affected areas, resulting in increased mortality from heart disease (myocardial infarction). The feasibility of continuing a temporary mechanical circulatory support (MCS) program is unknown. PURPOSE Our objective was to analyze the survival of patients requiring short-term MCS with veno-arterial extracorporeal membrane oxygenation (VA-ECMO) or Impella CP® during the COVID-19 pandemic. METHODS Retrospective study including all VA-ECMO and Impella CP® implants in a referral hospital since March 2020 compared to previous implants results. RESULTS Out of 167 short-term MCS implanted from 2013, 25 (15%) were conducted during the time of COVID-19 pandemic: 19 VA-ECMO and 6 Impella CP® (Table). Compared to preCOVID-19 implants, patients requiring MCS in the COVID era presented more frequently right ventricular dysfunction (p = 0.005) and showed a trend towards older age (p = 0.069) and lower left ventricular ejection fraction (p = 0.063), without other significant differences regarding the baseline situation and implant technique (Table). Encephalopathy was more frequent in the COVID-19 era, with no differences in other complications (Table). Survival at discharge was 43.7% in the pre-COVID era vs 36% during COVID-19 pandemic, without finding statistically significant differences (p = 0.313). CONCLUSION: Survival after temporary MCS did not get worse significantly during the COVID-19 pandemic. The possibility of short-term MCS should be maintained for cardiogenic shock and other cases of hemodynamic instability.